Optimasi Keuntungan Maksimum Dari Penjualan Seblak Dengan Menggunakan Metode Simpleks, Software POM-QM Dan Implementasi Rstudio - Tasia Maidi Saputri; Imelda Raudati; Pradita Eko Prasetyo Utomo; Ulfa Khaira (Universitas Katolik Widya Karya Malang, 2023)
This article aims to optimize the profit of seblak business through the application of Simplex method in linear program. Seblak is a popular business today with a wide variety of toppings such as meatballs, sausages, noodles, feet and many more, but efficient production planning and resource allocation can be challenging. In calculating this profit optimization, we use the Simplex method to identify production combinations that can generate maximum profit by considering various constraints related to raw materials, processing time, production costs to product selling prices. The result is expected to help seblak business owners in making smarter decisions regarding production, inventory, and pricing strategies, thus improving their business profitability.